Two New Species of Doliocarpus (Dilleniaceae) from Eastern Brazil, with an Emended Key for Species of Brazilian Atlantic Forest - Longhi Monzoli, João Victor [UNESP]; De Deus Felipe Araújo, Michelly; De Fraga, Claudio Nicoletti; Silveira, Daniela Sampaio [UNESP] (My University, 2022)
Doliocarpus is a neotropical genus with extensive representation in Brazil. During its taxonomic review, two new species from Brazilian Atlantic Forest were discovered and are herein described, illustrated, and compared to their close relatives. Doliocarpus heterophyllus can be recognized by its slightly undulate and subrevolute leaf margin along the lower third of the blade, with camptodromous venation, glabrous on the upper surface of the leaf, a cuspidate apex, and its glabrous fruit. Doliocarpus serrulatus has a serrulate leaf margin along the upper third of the blade, with craspedodromous venation, hirsute on the lower surface, and glabrous fruit. Diagnostic characters are discussed, accompanied by notes on their geographic distribution, informal conservation status, and photographs, and an emended key to all species of Doliocarpus of Atlantic Forest is also provided.
Keywords: Doliocarpus heterophyllus; Doliocarpus serrulatus; hotspot; IUCN Red List; lianas; taxonomy